Expert System for Diagnosis of Pests and Diseases of Citrus Plants using the Certainty Factor Method (Case Study in Deram Village, Karo Regency) - Everiyanti Br Tarigan (Institute of Computer Science, 2021)
This research is an expert system for the diagnosis of disease pests in citrus plants using the Certainty Factor Method. The Certainty Factor method is used to diagnose existing pests in citrus plants, which can be seen from the value of the symptoms obtained from citrus plant experts. This expert system research was built with Visual Basic 2010 application as a tool to diagnose disease pests in citrus plants, especially sweet oranges in the village of Deram, Karo Regency and use Microsoft Access 2010 as a database. The diagnosis results from this expert system are in the form of control as a solution to overcome and eradicate pests in citrus in Deram Village and this expert system aims to help citrus farmers, especially sweet oranges and the community, to identify pests in citrus.